The Study of Validity and Reliability of the SPOFIA Scale in Patients With Postoperative Breast Cancer. (October 2019) - Bozdemir, Havva; Aygin, Dilek
Introduction and aim: This study investigates the validity and reliability of the Subjective Perception of Post-Operative Functional Impairment of the Arm (SPOFIA) scale in patients with postoperative breast cancer. Materials and methods: Research was designed as a methodological type. Required permissions were taken from the ethics committee, relevant institutions, and researchers who developed the SPOFIA scale. Data were collected as a research in Kocaeli University hospital, between November 2017 and October 2018. For the Turkish SPOFIA scale's validity, data were collected from 142 patients. In the study, Patient Information Form, SPOFIA, and 36-item Short-Form Health Survey (SF-36) Quality-of-Life Questionnaire were used. In the analysis of data, descriptive statistical methods were used, and in the analysis of the validity of the scale, test-retest and Cronbach alpha reliability coefficient was used. Results: As a result of the analysis, we obtained Kendall W = 0.107, P  > 0.05; correlation with SF-36 was P  < .05, reliability studies test-retest analysis was P  > .05, and Cronbach alpha reliability coefficient was 0.739. It was determined that the SPOFIA scale was valid and reliable for Turkish patients and that the subjective findings of the patients could be used as individual follow-up in longitudinal monitoring. Conclusions: As a result, it was determined that the SPOFIA scale was reliable in the patient follow-up of breast cancer women.